2020
DOI: 10.1136/bmjmilitary-2019-001384
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C supplementation reduces the odds of developing a common cold in Republic of Korea Army recruits: randomised controlled trial

Abstract: IntroductionThe Republic of Korea (ROK) military has a high incidence of respiratory diseases at training centres. Vitamin C has been reported to reduce the incidence of colds. For the purpose of preventing soldiers' respiratory diseases, this study aimed to investigate whether vitamin C intake can prevent common colds in the ROK Army soldiers.MethodsThis was a randomised, placebo-controlled, and double-blind trial of soldiers who enlisted in the Korea Army Training Centre for 30 days from 12 February to 13 Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…Indeed, dietary antioxidants (VC and sulforaphane) were shown to decrease oxidative stress induced acute inflammatory lung injury in patients receiving mechanical ventilation [15]. In addition, oral VC (e.g., 6 g daily) was able to reduce viral infection risk [16] or to improve symptoms [17].…”
mentioning
confidence: 99%
“…Indeed, dietary antioxidants (VC and sulforaphane) were shown to decrease oxidative stress induced acute inflammatory lung injury in patients receiving mechanical ventilation [15]. In addition, oral VC (e.g., 6 g daily) was able to reduce viral infection risk [16] or to improve symptoms [17].…”
mentioning
confidence: 99%
“…On the other hand, randomized trials demonstrated that supplementation of vitamin C has positive effects on symptoms and on the duration of respiratory tract infections. Additionally, several data suggest that vitamin C can prevent pneumonia and improve its outcome, as well as other infections [ 122 , 123 , 124 , 125 ].…”
Section: Supplementationmentioning
confidence: 99%
“…Vitamin C has been proven to suppress the NFκB pathway in septic Gulo knockout mice [ 40 ] and modulate cytokine production [ 41 ]. Leukocytes isolated from vitamin C-treated guinea pigs expressed perfect chemotactic functions compared to control one [ 42 ].…”
Section: Plausible Intervention By Vitamin C Against Pathophysiologymentioning
confidence: 99%
“…Similar findings were observed among patients with severe influenza. In addition, oral vitamin C (6 g daily) was able to improve symptoms or reduce viral infection risk [ 41 100 ]. A recent Chinese study in severe COVID-19 patients has revealed the successful implementation of high dose intravenous vitamin C (10 - 20 g/day) in 50 patients, where the oxygenation index was normalized in real-time, thereby all patients recovered and were released after a certain period [ 110 ].…”
Section: Vitamin C: An Effective Consideration Against Covid-19?mentioning
confidence: 99%